Implikasi Putusan MK No. 94/PuuXxi/2023 terhadap Perlindungan Hak Pekerja atas Gugatan Daluwarsa Pemutusan Hubungan Kerja Berdasarkan Pasal 82 dan 97 Undang – Undang No. 2 Tahun 2004 Serta Pasal 159 Undang – Undang No. 13 Tahun 2003 - Muhammad Gerda; Irwan Saleh Indrapraja Indrapraja (Jurnal Hukum Lex Generalis, 2026)
This study examines Constitutional Court Decision Number 94/PUU-XXI/2023 which resolves legal uncertainty regarding the statute of limitations for filing Termination of Employment (PHK) lawsuits following the abolition of Articles 159 and 171 of the Manpower Law by the Job Creation Law. The MK Decision provides a new interpretation of Article 82 of the Industrial Relations Dispute Settlement Law (UU PPHI), stipulating that a PHK lawsuit may be filed within one year from the date the worker receives or is notified of the employer’s decision. This strengthens worker protection regarding severance compensation. For Article 97, the Court rejected the petition but emphasized the need for clear rulings on court fee reimbursement. Overall, the decision promotes legal certainty, norm harmonization and substantive access to justice for workers in PHK dispute resolution.